Energetic Electron Distributions Near the Magnetic Equator in the Jovian Plasma Sheet and Outer Radiation Belt Using Juno Observations. Issue 24 (21st December 2021) - Ma, Q.; Li, W.; Zhang, X.‐J.; Shen, X.‐C.; Daly, A.; Bortnik, J.; Mauk, B. H.; Kollmann, P.; Paranicas, C.; Becker, H. N.; Allegrini, F.; Kurth, W. S.; et al.
Abstract: We present the average distribution of energetic electrons in Jupiter's plasma sheet and outer radiation belt near the magnetic equator during Juno's first 29 orbits. Juno observed a clear decrease of magnetic field amplitude and enhancement of energetic electron fluxes over 0.1–1, 000 keV energies when traveling through the plasma sheet. In the radiation belts, Juno observed pancake‐shaped electron distributions with high fluxes at ∼90° pitch angle and whistler‐mode waves. Our survey indicates that the statistical electron flux at each energy tends to increase from M = 80 M=80 to M = 8 M=8 . The equatorial pitch angle distributions are isotropic or field‐aligned in the plasma sheet and gradually become pancake‐shaped at M < 15 M< 15 . The electron phase space density gradients at μ = 100 − 30, 000 μ =100-30, 000 MeV/G are relatively small at M > 30 M > 30 and become positive over 8 < M < 30 8< M< 30, suggesting the dominant role of adiabatic radial transport at higher M M shells, and the possible loss processes at lower M M shells. Plain Language Summary: Jupiter's strong magnetic fields trap high energy electrons in the magnetosphere and produce the most intense synchrotron radiation among solar system planets. The high energy electrons are transported from the outer and middle magnetosphere to the inner radiation belts and gain energy through multiple processes. We perform a survey of energetic electron distributions using Juno measurements near the magnetic equator at radial distances to Jupiter from 8 to 80 Jovian radii ( R J ). The electron flux distributions and magnetic field variations are different between the measurements in the plasma sheet and the radiation belts. The statistical electron fluxes tend to increase as the distance to Jupiter deceases from 80 R J to 8 R J near the magnetic equator. The electron pitch angle distributions are isotropic or field‐aligned at high radial distances and transitioning into a pancake distribution at radial distances below 15 R J . At radial distance larger than 30 R J, the electron distribution profile weakly depends on the radial distance suggesting a dominant adiabatic radial transport. At radial distance from 30 R J to 8 R J, the electron distribution profile suggests a source of energetic electrons from radial diffusion and loss of electrons closer to Jupiter. Key Points: Average electron fluxes over 0.1–1, 000 keV energies tend to increase from M = 80 to M = 8 near Jupiter's magnetic equator The energetic electron pitch angle distribution is isotropic or field‐aligned in the plasma sheet and becomes pancake‐shaped at M < 15 The radial gradient of electron phase space density at μ = 100–30, 000 MeV/G is positive at M < 30 and becomes smaller at M > 30